2022
DOI: 10.1097/corr.0000000000002328
|View full text |Cite
|
Sign up to set email alerts
|

What is the Accuracy of a Rapid Strip Test That Detects D-lactic Acid in Synovial Fluid for the Diagnosis of Periprosthetic Joint Infections?

Abstract: BackgroundD-lactic acid is a specific marker produced almost exclusively by bacterial species; thus, the appearance of this marker in synovial fluid may indicate periprosthetic joint infection (PJI). Recently, studies have investigated the accuracy of enzyme-linked laboratory tests that detect D-lactic acid in synovial fluid to diagnose PJI. However, to our knowledge, no studies have determined the usefulness of rapid strip tests that detect D-lactic acid in synovial fluid in the diagnosis of PJI.Questions/pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The authors concluded that a rapid off-label DLA strip test is valuable for diagnosing PJI, even though it has limitations, such as observer interpretation of the colorimetric aspect of the test and obliteration of the color change by blood. The study by Grzelecki et al [1] is important for several reasons. First, their work moves clinicians closer toward a specific, real-world practical information test.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 4 more Smart Citations
“…The authors concluded that a rapid off-label DLA strip test is valuable for diagnosing PJI, even though it has limitations, such as observer interpretation of the colorimetric aspect of the test and obliteration of the color change by blood. The study by Grzelecki et al [1] is important for several reasons. First, their work moves clinicians closer toward a specific, real-world practical information test.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Going forward, improved infection diagnosis will likely depend on identifying the unique biophysical properties of bacteria and its biofilm. We now know from Grzelecki et al [1] that DLA is unique to bacteria, and it can be used for the diagnosis of infection if the colorimetric limitations can be overcome and once we determine whether DLA production is universal across all bacteria.…”
Section: How Do We Get There?mentioning
confidence: 99%
See 3 more Smart Citations